The word after has become supposition from significant modal words. (Eurasian Journal of Philology Science and Education, 2015)
This article speaks about the sentences that are composed of modal words words. In Russian Education (linguistics ), in Turkish , in the Kasakh education were taken every opportunity to study the modales words.Modales words were also grouped according to meaning and significance. Among them have meaning, words such as: maybe, probably, but they were added to the modales words later than other words modales. Words are also found in the dialogues and complex sentences. Modales words in sentences blurts separately and intonation.This means that the modales words also includes a type of simple sentences modales. Words are also found in the main, subordinate clauses, and these words are found in the middle of sentences. In simple sentences they occur as the predicate, as incomplex sentences and clauses of the main words, and here, too, the modales words are found in the middle of sentences.
Keywords: sentences; compound sentences; modal words